Contextual Learning Mediated with Real Objects on Multiplication and division to Improve Motivation and Learning Outcomes - Sri Lestari (Jurnal Pendidikan Sains, 2014)
Pembelajaran Kontekstual Bermedia Objek Nyata pada Perkalian dan Pembagian untuk Meningkatkan Motivasi dan Hasil Belajar Abstract: The purpose of the study is to describe the implemtation of contextual learning real object of media on multiplication and division to increase motivation and learning outcomes of students fourth B grade at primary school Poncokusumo 01. The design of the study used action research. Collected data through were interviews, observations, questionnaires, and tests. The results of the study of 20 students, which was students’ motivation under the category of Good or Very Good in cycle I was 73,75%, in cycle II was 97,5%, increased to 23,75%. The average pre-action study was 58, student completed their 40%, in cycle I was 70%, in cycle II was 76,9, student completed 85%.Key Words: contextual learning, real object of media, motivation, learning outcome Abstrak: Tujuan penelitian adalah mendeskripsikan penerapan  pembelajaran kontekstual bermedia objek nyata pada perkalian dan pembagian untuk meningkatkan motivasi dan hasil belajar siswa kelas IVB SDN Poncokusumo 01. Rancangan penelitian menggunakan penelitian tindakan kelas. Pengumpulan data melalui wawancara, observasi, angket, dan tes. Hasil penelitian dari 20 siswa, pada siklus I siswa yang bermotivasi pada kategori baik atau sangat baik 73,75%, siklus II 97,5% meningkat  23,75%. Rata-rata hasil belajar pra tindakan 58, ketuntasan 40%, siklus I 70%, siklus II 76,9% ketuntasan 85%. Kata kunci: pembelajaran kontekstual, media objek nyata, motivasi, hasil belajar